Economic Status of women working in Pharmaceutical companies of Sikkim, India - Dangal, Subadra Devi; Chettri, Uday (Nepal Journal of Multidisciplinary Research, 2019)
The women have various responsibility in the family because they have to take care of children, family members and also have to involve in the outdoor activities to generate income. Participation on of women in economic activities is high in Sikkim. Women also play a major role in trending activities. So the study has explored the economic status of working women. The study was conducted in Sikkim among the 385 women working in Pharmaceutical companies. The structured survey questionnaire was used to collect the data. The collected data were statistically analysed and presented in the tabular form. The findings show that the majority (50.9%) working women were getting less than Rs. 10000/- per month from the service which was not adequate as their basic household needs. It is found from the that maximum percentage (84.2%) of respondents didn’t have any personal property in their name because of the society of patriarchal system and cultural practices of gender-based division of labour. The study suggests that concerned government and companies should enhance the capacity of working women and should increase their incentives considering the basic needs of workers.